Maritime enterprise and empire : Sir William Mackinnon and his business network, 1823-93 - Munro, J. Forbes (Woodbridge, Suffolk, UK ; Rochester, NY : Boydell Press, 2003)
This book explores the nineteenth century roots of globalisation through the activities of the enterprise network created by the Scottish merchant, William Mackinnon. It follows the rise of the family-led business group from its modest origins in Scotland to its transformation into the world's largest maritime and mercantile conglomerate, tracingthe history of the various shipping firms within the group - including the British India, Netherlands India and Australasian United companies - and identifies the key factors behind its domination of coastal steamshipping around the Indian Ocean and in.
18 Maritime enterprise and empireAppendix: family trees; Sources; INDEX
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Mackinnon, William, -- 1823-1893.; Wm. Mackinnon Co. -- History -- 19th century; Mackinnon, William, -- 1823-1893; Wm. Mackinnon Co; Steamboat lines -- Scotland -- History -- 19th century; Shipping -- Scotland -- History -- 19th century; Compagnies de navigation -- Écosse -- Histoire -- 19e siècle.; TRANSPORTATION -- Ships & Shipbuilding -- Pictorial; TRANSPORTATION -- Ships & Shipbuilding -- History; Shipping; Steamboat lines; Scotland; 1800-1899; Electronic books; History